The common motifs of spring festivals in the slavic and turkic worlds: maslenitsa and nevruz - Suiçer, Mehtap; Gökbayır, Tuğba (Ahmet BURAN, 2024)
Festivals are national, religious, or special days or periods that reflect a nation’s history, beliefs, traditions, and culture. Festivals, which exist in every nation around the world, are the product of a long-standing history from the past to the present. The Slavic and Turkic peoples, whose origins date back to ancient times, have many festivals, including religious, national, seasonal, and cultural ones. These festivals are important elements that keep society together and ensure solidarity in society. Maslenitsa, celebrated as a seasonal festival among the Slavic people, and Nevruz, celebrated among the Turkic people, are festivals symbolizing the end of winter and the transition to spring. Maslenitsa is the oldest Russian festival that has survived to the present day. The tradition of celebrating Maslenitsa dates back to the pre-Christian period. Nevruz, described as the Turkish spring festival, is an old festival that dates back to before the Turks accepted Islam. This article will examine the common elements of Maslenitsa and Nevruz, two seasonal festivals with shared characteristics among two distinct nations.

Bayramlar, bir milletin tarihini, inancını, geleneğini ve kültürünü yansıtan millî, dinî veya özel olarak önemi olan gün veya günlerdir. Dünya üzerinde her millette var olan bayramlar geçmişten günümüze süregelen köklü bir tarihin ürünüdür. Kökeni çok eski zamanlara uzanan Slav ve Türk milletleri dinî, millî, mevsimsel ve kültürel bayramlar olmak üzere birçok bayrama sahiptirler. Bu bayramlar toplumu bir arada tutan ve toplumda dayanışmayı sağlayan önemli unsurlardır. Slav halklarında bir mevsim bayramı olarak kutlanan Maslenitsa ve Türk halklarında kutlanan Nevruz Bayramı, kışın bitişi ve bahar mevsimine geçişi simgeleyen bayramlardır. Maslenitsa, günümüze kadar ulaşan en eski Rus bayramıdır. Maslenitsa kutlama geleneği, çok eski Hristiyanlık öncesi dönemlere kadar uzanmaktadır. Türk bahar bayramı olarak nitelendirilen Nevruz da Türklerin İslamiyeti kabulünden öncesine dayanan eski bir bayramdır. Bu makalede iki ayrı millette benzer özelliklere sahip mevsimsel bayramlar olan Maslenitsa ve Nevruz bayramının ortak unsurları ele alınacaktır.
SLAV VE TÜRK DÜNYASINDA BAHAR BAYRAMLARININ ORTAK MOTİFLERİ: MASLENİTSA VE NEVRUZ
Keywords: Modern Turkic Languages and Literatures (Other); Çağdaş Türk Lehçeleri ve Edebiyatları (Diğer)